An overview of Fischer-Tropsch Synthesis: XtL processes, catalysts and reactors - Martinelli, Michela; Gnanamani, Muthu Kumaran; LeViness, Steve; Jacobs, Gary; Shafer, Wilson D. (Applied catalysis. A, General, 2020)
[Display omitted] •An overview of recent techno-economic analyses on the utilization of natural carbon sources for syngas.•FT mechanisms, reactions and catalysts, if the catalyst surface energy favors CO hydrogenation to FT products.•An overview of the commercial scale reactor designs currently used in the FTS process. This review is divided into three main sections. The first section of this overview examines in detail recent techno-economic analyses on the utilization of biomass as a source of syngas for Fischer-Tropsch synthesis (FTS). FTS is a highly localized industry, and depends on the sources of syngas available, the products desired, and the demand for co- production of electricity. Where coal or natural gas coexist in the region where biomass is available, economics may favor producing or blending syngas from multiple resources, making biomass-to-liquids a highly complex scenario. Land use management is essential for sustainable biomass production, if used as the carbon source for FTS. The second section discusses FTS mechanisms, reactions and catalysts. Supposing the catalyst surface energy favors CO hydrogenation to FTS products, the sweet spot of FTS, selectivity will depend on the degree of back- donation from the metal. The degree of electron back-donation from the catalyst surface to both adsorbed CO and vinylic intermediates in part controls the FT synthesis product distribution. When the back-donation is sufficient, chain growth favors longer chained linear hydrocarbons (paraffins, alpha olefins, linear alcohols) suitable for upgrading to diesel, jet fuels, lubricants, and waxes. When back-donation is less significant, monomethyl branched hydrocarbons, internal olefins, and oxygenates (esters, acids and ketones) are elevated. Lastly, active supports are discussed for increasing the termination rate to oxygenates and olefins, as are hybrid catalysts that simultaneously carry out FTS and upgrading, often through secondary reactions. The last section provides an overview of the commercial scale reactor designs including the fixed bed, fluidized bed, and slurry bubble column reactor currently used in the FTS process. Economically, FTS is favored at larger scales; however, new compact reactor designs are coming into play aimed at monetizing highly localized (e.g. biomass) and stranded resources (e.g. natural gas). These types of reactors, involving microchannel and heat exchanger designs, must be highly efficient at managing heat, cost-effective, and mobile in order to exploit non-traditional sources of syngas.